Identitas dalam Kristus sebagai Fondasi Transformasi Sikap Hidup dan Keteladanan Umat - John Christ Dwiaprianto A; Yanto Paulus Hermanto; Victor Deak (KHARISMATA: Jurnal Teologi Pantekosta, 2026)
True Christian identity is the foundation that determines the direction of life and witness of believers. Since its mention in Antioch (Acts 11:26), the term "Christian" has emphasized Christlikeness. However, in the contemporary context influenced by materialism, moral relativism, and secularization, many believers experience an identity crisis, resulting in faith that stops at verbal confession without being realized in concrete behavior. This research applies qualitative methods through literature analysis, in which data are analyzed descriptively and analytically through biblical sources, classical and contemporary theological literature, and related academic studies. The results show that true Christian identity is rooted in a relationship with Christ and the Imago Dei, which guides believers to live holy, fruitful lives, and serve as examples in the family, church, and society. The restoration of Christian identity has ethical, ecclesiological, and missiological implications and is only possible through the renewing and strengthening work of the Holy Spirit. Thus, awareness of Christian identity becomes the foundation for restoring an authentic attitude to life and witness to faith in the modern world.     Identitas Kristen sejati merupakan dasar yang menentukan arah hidup dan kesaksian umat percaya. Sejak penyebutannya di Antiokhia (Kis. 11:26), istilah “Kristen” menegaskan keserupaan hidup dengan Kristus. Namun, dalam konteks kontemporer yang dipengaruhi materialisme, relativisme moral, dan sekularisasi, banyak orang percaya mengalami krisis identitas sehingga iman hanya berhenti pada pengakuan verbal tanpa diwujudkan dalam perilaku nyata. Penelitian ini menerapkan metode kualitatif melalui analisis kepustakaan, data dianalisis secara deskriptif-analitis melalui sumber Alkitab, literatur teologi klasik maupun kontemporer, serta kajian akademik terkait. Hasil penelitian menunjukkan bahwa identitas Kristen sejati bersumber pada hubungan dengan Kristus dan Imago Dei, yang menuntun umat untuk hidup kudus, berbuah, serta menjadi teladan di keluarga, gereja, dan masyarakat. Pemulihan identitas Kristen memiliki implikasi etis, eklesiologis, dan misiologi, serta hanya dimungkinkan melalui karya Roh Kudus yang memperbarui dan meneguhkan umat. Dengan demikian, kesadaran identitas Kristen menjadi fondasi pemulihan sikap hidup dan kesaksian iman yang autentik di tengah dunia modern.